Cornual ectopic pregnancy: laparoscopic management step by step. (28th March 2018) - Varun, Neha; Nigam, Aruna; Elahi, Arifa Anwar; Jain, Abhinav
Abstract : Cornual (interstitial) ectopic pregnancy is an uncommon type of ectopic pregnancy which is located in the interstitial part of the fallopian tube. It accounts for 2%–4% of all ectopic pregnancies. Cornual pregnancies often pose a diagnostic and therapeutic challenge with a significant high morbidity and mortality as a result of massive intraperitoneal bleeding. A case of unruptured cornual ectopic pregnancy in a patient with abnormal uterine bleeding is reported which was successfully managed laparoscopically.